Potential risk factors for diabetes mellitus type 1 - K. G. Korneva; L. G. Strongin; K. Yu. Nazarova; V. E. Zagainov (Сахарный диабет)
Diabetes mellitus type 1 (T1D) develops as a result of the interaction of genetic and environmental factors. Genetic predisposition to T1D turns into clinical reality only in half of hereditary cases, which indirectly indicates the importance of external factors, the significance of which is periodically reviewed. Retrospective and prospective clinical foreign and national studies were included. PubMed, Medline and eLibrary were searched. Modern ideas about the possible impact of the main prenatal and postnatal environmental factors on the development of autoimmune response against insulin-producing islet cells and T1D were discussed. The risk of developing type 1 diabetes is determined by the complex interaction of environmental factors and genetic predisposition. The mechanisms of their influence remain rather unknown. Further research is needed to determine strategies of primary and secondary prevention of T1D.